Dynamic Shifts in E-Commerce Consumption Patterns under Sectoral Inflationary Pressures and Fluctuating Consumer Sentiment - A. St. Fatmawaty; Deni Marsha (Smart International Management Journal, 2026)
The rapid expansion of e-commerce has transformed consumer purchasing behavior, particularly under conditions of sectoral inflation and volatile consumer sentiment. This study aims to examine how inflationary pressures across essential sectors—such as food, energy, and logistics—interact with changing consumer confidence to reshape online consumption patterns. Using a quantitative time-series approach, this study integrates macroeconomic indicators, consumer sentiment indices, and aggregated e-commerce consumption data in Indonesia to identify structural shifts in demand composition, purchasing frequency, and price sensitivity. The findings indicate that rising inflation in essential goods leads to substitution effects, where consumers prioritize necessities and reduce discretionary spending on online platforms. Furthermore, declining consumer sentiment amplifies cautious spending behavior, increasing reliance on discounts, digital promotions, and alternative payment schemes The study indicates that e-commerce consumption remains relatively adaptive despite macroeconomic uncertainty, particularly in digital services and essential goods categories, which maintain relatively stable demand despite economic pressures. In conclusion, the interaction between inflation and consumer sentiment significantly influences e-commerce dynamics, suggesting that digital marketplaces should adopt adaptive pricing strategies, personalized marketing, and flexible payment systems to sustain growth under uncertain economic conditions.